Optimum protein requirement of juvenile orange-spotted grouper (Epinephelus coioides) - Yan, Xiaobo (Sci Rep, 2021)
The purpose of subject was to explore the optimum protein requirement of juvenile grouper (Epinephelus coioides). In the test, 450 juveniles with an average weight (10.02 ± 0.22) g were randomly divided into six groups with triplicate, and were fed with 350, 400, 450, 500, 550 and 600 g/kg iso-lipid test diet twice 1 day for 8 weeks, respectively. The results showed that: (1) With the increase of protein level, the body weight gain rate and specific growth rate first increased and then reduced, while the feed coefficient rate first decreased and then increased, while the protein efficiency significantly decreased (P < 0.05). (2) With the increase of protein level, the condition factor, hepaticsomatic index and visceralsomatic index significantly reduced (P < 0.05). (3) With the increase of protein level, the crude protein content of whole fish and muscle gradually increased, while the crude lipid content gradually decreased. (4) High-protein diet (550–600 g/kg) significantly increased the plasma total protein content and decreased the triglyceride content of orange-spotted grouper (P < 0.05). (5) Compared with the 350 g/kg group, 500, 550, 600 g/kg groups significantly increased the activities of glutamic-pyruvic transaminase and glutamic oxaloacetic transaminase in liver (P < 0.05). (6) With the increase of protein level, the protease activity of intestine first increased and then decreased, and reached the maximum at the protein level of 500 g/kg, while lipase and amylase decreased significantly (P < 0.05). (7) The activities of acid phosphatase, superoxide dismutase and lysozyme in liver increased first and then decreased with the increase of protein level, and reached the maximum in the 400 g/kg protein group. According to the analysis specific growth rate, the optimum protein level of juvenile orange-spotted grouper is 521.84 g/kg.